MOOCs From the Viewpoint of the Learner: A Response to Perna et al. (2014). (May 2015) - Wiebe, Eric; Thompson, Isaac; Behrend, Tara
This response to Perna et al. provides an alternate approach to research on massive open online courses (MOOCs). We argue that a student-centered, theory-driven conceptualization and methodological approaches allow us to move beyond descriptive statistics and into a deeper understanding of MOOC learners. Examples using a teacher development MOOC are presented.